Study on socio-demographic determinants of knowledge and practice regarding road safety among medical students of CIMS, Bilaspur (C.G.) - Sharma, Vivek; Kawale, Shailesh K.; Thakur, Hemlata (International Journal Of Community Medicine And Public Health, 2018)
Background: An accident has been defined as an unpremeditated event resulting in recognizable damage. Youths constitute the most vulnerable group to get into the road traffic accidents so they need significant level of awareness and realization of their knowledge gap regarding road safety measures. The aims and objectives of the study were to find out the level of knowledge about road traffic signs; to assess the practice of medical students towards road traffic rules Methods: A cross sectional study was conducted among willing undergraduate M.B.B.S. students enrolled in CIMS, Bilaspur. We recorded verbal response of participants by interview with the use of pre designed & pre tested questionnaire. Results: Total 289 students were participated in our study. 139 were female and 150 were male, 75 students were below 20 year of age, 89 were living with their parents. In our study we found that student’s age >20 years have more knowledge (36%) of road traffic signs than students aged ≤20 years (28%). Boys have more knowledge (36.66%) of road traffic signs than girls (30.93%). Students living without parents have more knowledge of road traffic signs over students living with their parents. More sensible practice was seen in students >20 years of age, more careful practice seen in male over female and more responsible practice was seen in students living with their parents. Conclusions: The level of knowledge regarding road signs and symbol among study participants was not satisfactory. But regarding practice most of the participants were using the safety measures occasionally.